2019
DOI: 10.1186/s12936-019-2810-2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Plasmodium homocircumflexum virulence in experimentally infected passerine birds

Abstract: Background Avian malaria parasites (genus Plasmodium ) are cosmopolitan and some species cause severe pathologies or even mortality in birds, yet their virulence remains fragmentally investigated. Understanding mechanisms and patterns of virulence during avian Plasmodium infections is crucial as these pathogens can severely affect bird populations in the wild and cause mortality in captive individuals. The goal of this study was to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 49 publications
(68 reference statements)
3
39
0
2
Order By: Relevance
“…also show erythrocytic schizogony. merozoites from erythrocytic and exo-erythrocytic schizonts can initiate secondary exo-erythrocytic schizogony, forming phanerozoites, which often develop in endothelial cells lining the capillaries 110,119,120 . massive infestation of bone marrow cells by phanerozoites often occurs during infection of birds with Plasmodium elongatum and some other species 110,111,121 .…”
Section: Box 1 | Evolution Of a Haematopoietic Reservoir In Plasmodiumentioning
confidence: 99%
See 1 more Smart Citation
“…also show erythrocytic schizogony. merozoites from erythrocytic and exo-erythrocytic schizonts can initiate secondary exo-erythrocytic schizogony, forming phanerozoites, which often develop in endothelial cells lining the capillaries 110,119,120 . massive infestation of bone marrow cells by phanerozoites often occurs during infection of birds with Plasmodium elongatum and some other species 110,111,121 .…”
Section: Box 1 | Evolution Of a Haematopoietic Reservoir In Plasmodiumentioning
confidence: 99%
“…P. elongatum can cause dyserythropoiesis and anaemia due to damage of bone marrow cells 111,122 . The ability of erythrocytic and exo-erythrocytic merozoites to initiate secondary exo-erythrocytic schizogony in avian and reptile parasites opens opportunities for experiments on the tissue stages by inoculation of infected blood, avoiding the use of vectors 119 . Blood schizogony is only reported for Plasmodium spp.…”
Section: Box 1 | Evolution Of a Haematopoietic Reservoir In Plasmodiumentioning
confidence: 99%
“…Additional experimental infections of canaries with pLINN1 could help confirm differences between P. giovannolai and P. matutinum pLINN1 regarding the location of tissue stage formation. It is worth mentioning that the same Plasmodium strain might be markedly different in the ability to produce phanerozoites in the brain of different avian host species [87], so this feature should be used carefully in taxonomic research.…”
Section: Subgenus Haemamoebamentioning
confidence: 99%
“…In contrast, infection of immunologically naïve host species regularly results in severe morbidity and has caused mortalities in several non-passerine bird species [10][11][12][13][14][15][16][17][18]. However, several experimental infection studies demonstrated also high susceptibility of passerine bird species to certain haemosporidian parasites and markedly different pathogenicity depending both on infected host species and parasite strain [19][20][21][22][23]. Moreover, few reports showed lethal infections with Plasmodium spp.…”
Section: Introductionmentioning
confidence: 99%